Phytase from antarctic yeast strain Cryptococcus laurentii AL27 - Pavlova, K; Gargova, S; Hristozova, T; Tankova, Z (Folia microbiologica, 2008)
Cryptococcus laurentii strain AL27 demonstrating significant potential for intracellular phytase production was selected by 2-step screening of Antarctic yeasts. The strain showed increased phytase activity in a culture medium with 40 g/L sucrose, KH2PO4 providing 5 mg/L phosphorus, and cultivation temperature of 24 degrees C, which relates it to psychrotrophic microorganisms. The enzyme kinetic characteristics according to sodium phytate were Km = 0.98 mmol/L, vlim = 33.3 micromol g(-1) min(-1). The enzyme had maximum activity at 40 degrees C and acted within a wide pH range: from 2.0 to 5.5, which is of positive significance for its direct inclusion into the feed of monogastric animals.
Keywords: teplota; 6-Phytase; Antarctic Regions; Kinetics; Cryptococcus; Soil Microbiology; Antarktida; stabilita enzymů; Enzyme Stability; kinetika; Temperature; fungální proteiny; 6-fytasa; půdní mikrobiologie; Fungal Proteins